Legislasi Syariah Card: Implementasi Dalam Kompilasi Hukum Ekonomi Syariah Dan Fatwa Dewan Syariah Nasional Majelis Ulama Indonesia - Riyadi, Riyadi; Hermawan, Yudi (Universitas Islam Negeri Raden Intan Lampung, 2021)
Sharia Card (syaria card) is one of the new products of Islamic banking, so that its application in financial transactions needs special attention so that its implementation remains in accordance with the concept of sharia. Issuance of Sharia Cards is very beneficial for humans, namely making it easier for humans to make payments, and giving humans a sense of security. However, besides that, Indonesia as a country based on law needs to prepare a clear and detailed positive legal basis related to the emergence and trend of increasing use of the Sharia Card in Indonesia. There is a need for legal arrangements that do not tend to be rigid and lagging behind with harmonization between the Compilation of Sharia Economic Law, the Fatwa of the National Sharia Council of the Indonesian Ulema Council and the Financial Services Authority Regulations governing the implementation of Sharia Cards in Islamic financial institutions in Indonesia. This research is an attempt to describe the extent to which legal arrangements in Indonesia regulate Sharia Cards in the Compilation of Sharia Economic Law, the Fatwa of the Sharia Council of the Indonesian Ulema Council, and the Regulations of the Financial Services Authority. It is hoped that this research can be useful as information for Islamic financial institutions and the public, especially legal practitioners in Indonesia in handling legal cases that occur around the implementation of the Sharia Card in Indonesia. This research includes library research (Library Research), which is a research conducted by collecting library materials, reading books, literature and examining various kinds of theories that have a relationship with the problem under study.Keywords: Sharia Card, Sharia Card, Sharia Economic Law